2017
DOI: 10.1007/s10803-017-3260-8
|View full text |Cite
|
Sign up to set email alerts
|

Proneness to Self-Conscious Emotions in Adults With and Without Autism Traits

Abstract: Self-conscious emotions, such as shame, guilt and pride, facilitate our social interactions by motivating us to adhere to social norms and external standards. In this study, we examined proneness to shame, guilt, hubristic pride and authentic pride in adults with Autism Spectrum Disorder traits (ASD-T) and in neurotypical (NT) adults. Relations between proneness to self-conscious emotions and theory of mind (ToM), fear of negative evaluation, and social functioning were also assessed. Adults with ASD-T showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 67 publications
3
17
0
1
Order By: Relevance
“…Williams and Happé [] also found that self‐conscious emotions (e.g., pride, guilt) were more difficult for children with ASD to accurately define and report examples of than basic emotions (e.g., happiness, scared). Finally, and perhaps more closely connected to the goals of the present study, recent research has shown that adults with ASD traits (ASD‐T) exhibit more proneness to shame and externalization, and less proneness to guilt, hubristic pride and authentic pride than neurotypical adults [Davidson, Vanegas, & Hilvert, ]. It is not known whether a similar pattern would be found in children.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Williams and Happé [] also found that self‐conscious emotions (e.g., pride, guilt) were more difficult for children with ASD to accurately define and report examples of than basic emotions (e.g., happiness, scared). Finally, and perhaps more closely connected to the goals of the present study, recent research has shown that adults with ASD traits (ASD‐T) exhibit more proneness to shame and externalization, and less proneness to guilt, hubristic pride and authentic pride than neurotypical adults [Davidson, Vanegas, & Hilvert, ]. It is not known whether a similar pattern would be found in children.…”
Section: Introductionmentioning
confidence: 57%
“…Related to the present study, Heerey, Keltner, and Capps [] found that ToM was positively related to the ability to recognize self‐conscious emotions in both children with and without ASD. In a similar vein, research has shown that ToM skills were positively related to proneness to guilt, shame and pride in adults with Autism Spectrum Disorder Traits [ASD‐T; Davidson et al, ]. In contrast, ToM skills were found to be negatively related to proneness to shame in neurotypical adults, but positively related in adults with ASD‐T [Davidson et al, ].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations